Keragaman dan daya hasil lima aksesi ubi kayu lokal (Manihot esculenta Crantz) asal Kampung Yammua Arso 6, Distrik Arso Barat, Kabupaten Keerom, Papua - Wibawati, Zarima; A. Merahabia, Paskalius; Lenda Mawikere, Nouke; Prabawardani, Saraswati; Litaay, Gabriela Welma (Program Pascasarjana Universitas Papua, 2025)
ABSTRACT: This study aims to identify and analyze the diversity and yield potential of several local cassava accessions originating from Yammua Village, Arso 6. The research was conducted in Yammua Village, Arso 6, West Arso District, Keerom Regency, Papua Province, from July 2023 to March 2024. Evaluation of cassava germplasm was carried out using a Randomized Block Design (RBD) with five cassava accessions and three replications, resulting in a total of 15 experimental units. Observations were made on three samples from each experimental unit based on the description by Fukuda (2010). Agronomic variables observed included plant height, stem diameter, tuber diameter, tuber length, number of tubers per plant, tuber weight per plant, number of commercial tubers, commercial tuber weight, number of tubers per ridge, tuber weight per ridge, and harvest index. Data analysis included Analysis of Variance (ANOVA), Principal Component Analysis (PCA), Cluster Analysis, and Correlation Coefficient analysis. The results showed significant differences among the five evaluated accessions in terms of plant height, tuber diameter, number of tubers per plant, tuber weight per plant, number of commercial tubers, commercial tuber weight, number of tubers per plot, tuber weight per plot, and harvest index. The similarity coefficient among accessions ranged from 0.07 to 0.33. Two principal components successfully explained 89.7% of the total variation. A significant positive correlation was found between harvest index, tuber diameter, tuber weight per plant, number of commercial tubers, and commercial tuber weight with yield.